2020
DOI: 10.1007/s11205-020-02551-0
|View full text |Cite
|
Sign up to set email alerts
|

So Far, so Similar? Labour Market Feminization in Italy and Chile

Abstract: The article aims to analyse gender segregation in the labour market while comparing two national contexts in Europe and Latin America. Specifically, it will consider the growth trends of female employment in the last 25 years (1992–2017), its distribution between activity sectors and occupations, and the gender pay gap. Feminization models and gender inequalities are framed within labour market segmentation theories, which are in partial contrast to human capital theories and neoclassical economics. The initia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 14 publications
0
3
0
5
Order By: Relevance
“…Nivel de segregación laboral similar entre estos países aun cuando son contextos económicos, políticos y sociales distintos (Semenza, 2021). Género y envejecimiento en el trabajo en Chile: empleo, condiciones laborales, conciliación y salud de hombres y mujeres en una fuerza laboral que envejece.…”
Section: Categoría Artículos Resultadosunclassified
See 1 more Smart Citation
“…Nivel de segregación laboral similar entre estos países aun cuando son contextos económicos, políticos y sociales distintos (Semenza, 2021). Género y envejecimiento en el trabajo en Chile: empleo, condiciones laborales, conciliación y salud de hombres y mujeres en una fuerza laboral que envejece.…”
Section: Categoría Artículos Resultadosunclassified
“…Se identifican barreras culturales que provienen de la división sexual del trabajo y reproducidas constantemente por mecanismos institucionales y de mercado, que derivan en acentuadas condiciones de precariedad, inestabilidad e informalidad laboral (Espino y Sauval, 2016). Un estudio comparativo del índice de segregación laboral de Chile e Italia, dos contextos socioeconómicos distintos, indica que el índice de segregación es similar en ambos países, a pesar de las diferencias significativas en los contextos socioeconómicos e institucionales (Semenza, Boccardo y Sarti, 2021).…”
Section: Segregación Laboralunclassified
“…Therefore, professional females’ satisfaction with their career can reflect their evaluation of the overall employment environment. (5) Salary satisfaction in the context of social development reveals that the external inequality experienced by women is largely reflected in the gender difference in salary ( Boyer and England, 2008 ; Yao et al, 2017 ; Semenza et al, 2021 ), even though the labor participation rate of Chinese women is higher than the world average, the gender gap in pay still exists. Therefore, salary satisfaction can be used to measure gender equality at the workplace.…”
Section: Theoretical and Realistic Basismentioning
confidence: 99%
“…On the one hand, it has been shown that the pay employees receive is partly based on the extent to which their abilities match the demands of an occupation and the expectations of their work environment and employer [ 38 , 39 ]. Thus, employees working in a gender-typical occupation may be rewarded for fitting in, even more so as employment conditions, the work environment, and last but not least, the wage structure are to a large extent regulated by employers and their attitudes [ 40 ]. This association is also supported by Social Role Theory [ 41 , 42 ]: Violations of gender-based expectations are often punished and may lead to social and economic disadvantages [ 43 45 ].…”
Section: Introductionmentioning
confidence: 99%